The effect of Nira Lontar (Borassus flabellifer Linn) Probiotic Fluid Offered With Multilevel Dosage to Weight and Histopathologic of Broiler Duodenum - Lazarus Raya Beda; Herlina U Detha; Antin YN Widi (Jurnal Veteriner Nusantara, 2020)
Broiler chickens is one type of livestock that can be choose that means to increase the availability of animal protein for Indonesian people. Probiotics that giving in feed and drinking water can suppress mortality and increase livestock productivity. This research is a laboratory experimental research with Post Test Randomized Control Group research design. Treatment for this experimental is to offer lontar palm juice to broiler chickens. The sampling method uses the Simple Random Sampling method because the sample is taken randomly from the population so that all members of the population have equal opportunity to be selected as sample and grouped in 5 groups. After the treatment of each broiler chicken in the group was euthanatic by heart embolization techniques, broilers has been necropsed and duodenum has collected into pots that containing 10% Formalin. The duodenal organ is then sent to Prof DR WZ Johanes Hospital for histopathology preparations and Hematoxiline Eosin (HE) staining. The results of this study can be concluded that the offered of 1 ml/liter Nira Lontar (Borassus flabellifer Linn) probiotic fluid is the optimum dose for broiler weight gain, Nira Lontar(Borassus flabellifer Linn) probiotic fluid 1 ml / liter of water can improve feed efficiency and low FCR levels in broiler, offered of Nira Lontar (Borassus flabellifer Linn) probiotic fluid with multilevel doses (1 ml / liter of water, 2 ml / liter of water, 4 ml / liter of water and 8 ml / liter of water) with 14 day interval time is still safe because there is no histological structure change in broiler duodenum.